The Mammoth book of SF stories by women (Robinson/Running Press, 2014)
This anthology showcases the most exceptional science fiction stories written by women in recent decades, from classic stars like Ursula K. Le Guin and James Tiptree Jr. to science-fiction greats such Nancy Kress, Lois McMaster Bujold, and Karen Joy Fowler to new award-winning talents.